The Cambridge history of Inner Asia the Chinggisid Age - Di Cosmo, Nicola; Frank, Allen J.; Golden, Peter B. (Cambridge University Press, 2009)
In this book, a team of international scholars examine the rise, fall, and legacy of the Mongol world empire.